Cardo polyimides with high Tg and transparency derived from bisphenol fluorenes and 1, 4-bis(4-fluorophthalimide)cyclohexanes via aromatic nucleophilic substitution. (20th April 2023) - Chen, Guofei; Xu, Gang; Jiao, Yang; Tang, Yongmei; Tan, Liyun; Fang, Xingzhong
Graphical abstract: Highlights: Two series of cardo polyimides with high T g s and high transparency were prepared. A new method to prepare PIs with alicyclic diamine to avoid salt formation was provided. The DMPF base polyimide PI-IIa displayed high thermal properties with T g of 350 ℃ and high transparency with transmittance of 86% at 400 nm. Abstract: Two series of transparent cardo polyimides (PIs) derived from bisphenol fluorenes and 1, 4-bis(4-fluorophthalimide)cyclohexanes (BFCH) with different ratios of trans- and cis - 1, 4-diaminocyclohexane were prepared via aromatic nucleophilic substitution. These PIs exhibited high glass transition temperatures ( T g s) of 271–352 °C, 5% weight loss temperatures ( T d 5% ) of 400–433 °C in nitrogen, mechanical properties of tensile strengths of 62–107 MPa, tensile moduli of 3.0–4.4 GPa and elongations at break of 1.7–4.5% and great solubility in a variety of organic solvents. These PI films appeared excellent optical transparency, which displayed the cut-off wavelengths from 323 to 355 nm and high transmittance at 450 nm with more than 85 %. The steric effects of different substituent groups on bisphenol fluorene and different ratios of trans / cis configuration were also investigated.